The role of individual differences in the development and transfer of writing strategies between foreign and first language classrooms. Issue 4 (4th July 2019) - Forbes, Karen
Abstract: While the importance of considering the wide variation among language learners has been brought to the forefront in recent years, the impact of such individual differences on the process of second or foreign language writing has been largely neglected. This paper aims to explore the ways in which individual students develop and transfer strategies within and between foreign language (FL) and first language (L1) writing. A two-phase intervention of strategy-based instruction was conducted primarily in the FL German classroom, and later also in the L1 English classroom of a Year 9 (age 13–14) class in a secondary school in England. This paper draws on in-depth qualitative data from writing tasks and stimulated recall interviews. A range of students' trajectories through the intervention were evaluated and four distinct writer 'profiles' were identified: the strategic writer, the experimenter, the struggling writer and the multilingual writer. Both the development and transfer of strategies for these students were shown to be influenced by a complex and dynamic range of factors such as the learner's proficiency level, their level of metacognitive engagement with the task, their attitude towards writing and their strategic use of other languages in their repertoire.